Real-World Clinical Data of Palbociclib in Asian Metastatic Breast Cancer Patients: Experiences from Eight Institutions - Lee, Jieun; Park, Hyung Soon; Won, Hye Sung; Yang, Ji Hyun; Lee, Hee Yeon; Woo, In Sook; Shin, Kabsoo; Hong, Ji Hyung; Yang, Young Joon; Chun, Sang Hoon; Byun, Jae Ho (Cancer Research and Treatment, 2021)
PurposeUse of cyclin-dependent kinase 4/6 inhibitors improved survival outcome of hormone receptor (HR) positive metastatic breast cancer (MBC) patients, including Asian population. However, Asian real-world data of palbociclib is limited. We analyzed the real-world clinical practice patterns and outcome in HR-positive, MBC Asian patients treated with palbociclib. Materials and MethodsBetween April 2017 to November 2019, 169 HR-positive, human epidermal growth factor-2–negative MBC patients treated with letrozole or fulvestrant plus palbocilib were enrolled from eight institutions. Survival outcome (progression-free survival [PFS]), treatment response and toxicity profiles were analyzed. ResultsMedian age of letrozole plus palbociclib (145 patients, 85.8%) and fulvestrant plus palbociclib (24 patients, 14.2%) was 58 and 53.5 years, with median follow-up duration of 14.63 months (range 0.2 to 33.9 months). Median PFS (mPFS) of letrozole plus palbociclib and fulvestrant plus palbociclib was 25.6 (95% confidence interval [CI], 19.1 to not reached) and 6.37 months (95% CI, 5.33 to not reached), comparable to previous phase 3 trials. In letrozole plus palbociclib arm, luminal A (hazard ratio, 2.86; 95% CI, 1.20 to 6.80; p=0.017) and patients with good performance (Eastern Cooperative Oncology Group 0-1 [hazard ratio, 3.68; 95% CI, 1.70 to 7.96]) showed better mPFS. In fulvestrant plus palbociclib group, chemotherapy naïve patients showed better mPFS (hazard ratio, 12.51, 95% CI, 1.59 to 99.17; p=0.017). The most common grade 3 or 4 adverse event was neutropenia (letrozole 86.3%, fulvestrant 88.3%).ConclusionTo our knowledge, this is the first real-world data of palbociclib reported in Asia. Palbociclib showed comparable benefit to previous phase 3 trials in Asian patients during daily clinical practice.